Korelasi Antara Kemampuan Pemahaman IT Orang Tua Murid Terhadap Nilai Siswa SD Se Kelurahan Sekarteja Pada Pembelajaran Daring - M. Rudi Gunawan P; Fadma Rosita (Peneliti.net, 2021)
The current pandemic that is engulfing the world has had a profound impact on institutions in the world. education. So that the learning process during the pandemic is carried out with a bold system. Courage-based learning is also carried out by schools in elementary schools in the Sekarteja village, East Lombok. So this research was conducted in the Sekarteja sub-district which has three schools, namely SD N I, 2, and 3 Sekarteja. The author conducted this study in order to correlate IT skills with learning outcomes, by comparing the values ​​obtained before bold learning and after daring learning in the same subject. The data was obtained by providing an online questionnaire which was distributed through the walisiswa Whatsapp group. Questionnaire value data obtained through the SPSS application. The author processes the data with the analysis of Descriptive Statistics Frequencies in processing the data that has been processed so that it becomes the average value of the subjects related to the value components: questionnaire scores, B. Indonesian subjects scores, Subject scores, Natural Sciences, subjects scores, Mathematics, Social Studies subjects scores, and mean scores before bold learning on similar subjects. Bivariate correlation analysis was used to compare the average value on the map concerned in the face-to-face learning and learning process with the aim of classifying the results of data processing into criteria to become information and evaluation. The criteria made by the author are: very less 0-25, less 26-50, enough 51-75, good 76-100. This research is carried out so that schools can find out the correlation of courageous learning with student learning outcomes, so that schools can make improvements to the bold learning system.